Impact of Periprocedural Colchicine on Postprocedural Management in Patients Undergoing a Left Atrial Appendage Ligation Using LARIAT. (11th December 2015) - GUNDA, SAMPATH; REDDY, MADHU; NATH, JAYANT; NAGARAJ, HOSAKOTE; ATOUI, MOUSTAPHA; RASEKH, ABDI; ELLIS, CHRISTOPHER R.; BADHWAR, NITISH; LEE, RANDALL J.; DI BIASE, LUIGI; MANSOUR, MOUSSA; RUSKIN, JEREMY N.; et al.
Periprocedural Colchicine for Epicardial Access Procedures: Introduction: Left atrial appendage (LAA) can be effectively and safely excluded using a novel percutaneous LARIAT ligation system. However, due to pericardial catheter manipulation and LAA ligation and subsequent necrosis, postprocedural course is complicated by pericarditis. We intended to evaluate the preprocedural use of colchicine on the incidence of postprocedural pericardial complications. Methods and Results: In this multicenter observational study, we included all consecutive patients who underwent LARIAT procedure at the participating centers. Many patients received periprocedural colchicine at the discretion of the physician. We compared the postprocedural outcomes of patients who received prophylactic periprocedural colchicine (colchicine group) with those who did not receive colchicine (standard group). A total of 344 consecutive patients, 243 in the "colchicine group" and 101 in the "standard group, " were included. The mean age, median CHADS2VASc score, and HASBLED scores were 70 ± 11 years, 3 ± 1.7, and 3 ± 1.1, respectively. There were no significant differences in major baseline characteristics between the two groups. Severe pericarditis was significantly lower in the "colchicine group" compared to the "standard group" (10 [4%] vs. 16 [16%] P<0.0001). The colchicine group, compared to the standard group, had lesser pericardial drain output (186 ± 84 mL vs. 351 ± 83, P<0.001), shorter pericardial drain duration (16 ± 4 vs. 23 ± 19 hours, P<0.04), and similar incidence of delayed pericardial effusion (4 [1.6%] to 3 [3%], P = 0.42) when compared to the standard group. Conclusion: Use of colchicine periprocedurally was associated with significant reduction in postprocedural pericarditis and associated complications.